Temporal trends in spontaneous reporting of unlabelled adverse drug reactions - Haramburu, Françoise (1997)
Aims Trends in spontaneous reporting during the first years on the market were analyzed from a sample of selected drugs, with special attention to unlabelled effects. Methods Ten drugs were selected giving rise to approximately 100 spontaneous reports each during the first 4 years of marketing. Case reports were identified from the national pharmacovigilance database. A bibliographical score assigned at the time of reporting was used to identify unlabelled effects. Results were expressed as reporting rates. Results The average reporting rate peaked during the first year of marketing (54.6 per million treatment-months; s.d.:62.8), then progressively decreased during the following years. Unlabelled effects represented 63% of all the spontaneous reports during the first year. Conclusions Unlabelled adverse effects represent a high proportion of spontaneous reports during the early years of marketing.